General characteristics of the diet of Trachinotus paitensis (Teleostei: Carangidae) from San Ignacio Lagoon, Baja California Sur, Mexico - V.H. Cruz Escalona; L.A. Abitia Cárdenas (Revista de Biología Tropical, 2004)
The food habits of Trachinotus paitensis, in San Ignacio Lagoon B.C.S., Mexico, were investigated. We observed that T. paitensis is carnivorous, feeding mainly on benthic invertebrates (the gastropods Anachis spp., Bittium spp., and the crustacean larvae). We concluded that T. paitensis is an opportunist predator that impacts mainly on epibenthic invertebrates Fueron investigados los hábitos alimenticios de Trachinotus paitensis, en la laguna San Ignacio B.C.S., México. Se observó que T. paitensis es carnívoro, y se alimenta principalmente de invertebrados bénticos (los gastrópodos Anachis spp., Bittium spp., y larvas de crustáceos). En conclusión esta especie es un depredador oportunista que tiene un impacto principalmente sobre las poblaciones de invertebrados epibénticos